COVID-19 and Emergency Migration to Remote Teaching in a Public University in the Maldives: Challenges, Solutions, and Lessons Learned - Dheeba Moosa; Visama Hassan (Journal of Economy Culture and Society)
Institutions of higher education worldwide were forced to implement emergency remote teaching (ERT) during the COVID-19 pandemic. This scenario presented several issues for university lecturers and students. This study examines the challenges, experiences, and lessons learned by lecturers at a public university in the Maldives when forced to conduct ERT during the pandemic using an exploratory sequential mixed-method. The respondents most frequently cited unreliable internet connection (83.9%) and internet cost (76.8%), while 75% reported difficulty in motivating students and meeting their varied needs (64.3%). Access to technology (66.1%) and performance assessment (62.5%) were also mentioned. Challenges included internet, technology, student support, learning, and evaluation. The lecturers learned new skills during the pandemic, which was a positive outcome. Lastly, they stressed training, assistance, and the crisis readiness of the university.